Analytical expressions for calculations of scattered neutrons from the sample (scatterer) at small angles - О. О. Gritzay; А. K. Grymalo; V. A. Pshenychnyi (Ядерна фізика та енергетика)
Analytical expressions for calculation of yield of scattered neutrons from the two-component sample СН2 at the angles of 15, 20, 25 and 30° were received. The analysis of the range of validity of the obtained expressions depending on the structure of investigated cross sections was carried out.